2019
DOI: 10.25259/apos_20_2019
|View full text |Cite
|
Sign up to set email alerts
|

Tomographic mapping of buccal shelf area for optimum placement of bone screws: A three-dimensional cone-beam computed tomography evaluation

Abstract: Introduction: Buccal shelf bone screws have become increasingly popular as a preferred method of skeletal anchorage in the mandibular arch. Anatomic variations and clinical experience suggest that width and slope of the bone at buccal shelf vary in different population groups, with some individual variations. Aims and Objectives: The objective of this study was to evaluate angulation of the bone screw of mandibular buccal shelf area, total bone width, thickness of the cortical bone, and proximity to neurovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Nucera et al 13 found values of 7.88 ± 1.71 mm on the right side and 7.71 ± 1.69 mm on the left side. Kolge et al 19 determined a thickness of 6.40 ± 1.35 mm at 8 mm from CEJ at the distobuccal cusp of the mandibular second molar, while Elshebiny et al 12 documented a value of 8.13 ± 1.97 mm at the same location. The present study also found greater bone thickness at the distal surface of the mandibular second molar, with an average value of 7.6 ± 1.6 mm at 11 mm from CEJ.…”
Section: Discussionmentioning
confidence: 99%
“…Nucera et al 13 found values of 7.88 ± 1.71 mm on the right side and 7.71 ± 1.69 mm on the left side. Kolge et al 19 determined a thickness of 6.40 ± 1.35 mm at 8 mm from CEJ at the distobuccal cusp of the mandibular second molar, while Elshebiny et al 12 documented a value of 8.13 ± 1.97 mm at the same location. The present study also found greater bone thickness at the distal surface of the mandibular second molar, with an average value of 7.6 ± 1.6 mm at 11 mm from CEJ.…”
Section: Discussionmentioning
confidence: 99%
“…Correia et al (14) found 7.6±1.6mm at 11mm CEJ, Nucera et al (7) reported 7.88±1.71mm on the right side and 7.71±1.69mm on the left side. While other authors found slightly lower values, but they measured 8mm from the CEJ (9,25).…”
Section: Discussionmentioning
confidence: 78%
“…Elshebiny et al studied the anatomy of the MBS by superimposing the STL models of the subjects on their CBCTs and virtually placing miniscrews after digitally tracing the inferior alveolar canal and also reported the greatest buccal and cortical bone depth distal to the 2nd molar at 8 mm from the CEJ [ 24 ]. Another study by Kolge et al studied the MBS at three different locations and two heights from CEJ and concluded that the DB2M region at 8 mm depth from the CEJ had the highest TBT (6.4mm) with the advocation of pre-drilling in cases of thick cortical bone which will result in the delayed failure of the miniscrew [ 25 ]. Trivedi et al also reported greater CBT of 7 mm vertically from the alveolar crest at DB2M region and emphasizes caution while placing MS at this anatomic site due to its close proximity to the inferior alveolar nerve [ 20 ].…”
Section: Discussionmentioning
confidence: 99%